Novel 'Candidatus Liberibacter' species identified in the Australian eggplant psyllid, Acizzia solanicola. Issue 4 (7th April 2017) - Morris, Jacqueline; Shiller, Jason; Mann, Rachel; Smith, Grant; Yen, Alan; Rodoni, Brendan
Summary: A novel candidate species of the liberibacter genus, ' Candidatus Liberibacter brunswickensis' (CLbr), was identified in the Australian eggplant psyllid, Acizzia solanicola . This is the first discovery of a species belonging to the liberibacter genus in Australia and the first report of a liberibacter species in the psyllid genus Acizzia . This new candidate liberibacter species has not been associated with plant disease, unlike other psyllid‐vectored species in the genus including ' Candidatus Liberibacter asiaticus ' (CLas), ' Candidatus Liberibacter africanus' (CLaf) and ' Ca . Liberibacter solanacearum' (CLso). This study describes novel generic liberibacter genus primers, used to screen Australian psyllids for the presence of microflora that may confound diagnosis of exotic pathogens. CLbr forms a unique clade in the liberibacter genus based on phylogenetic analysis of the 16S ribosomal ribonucleic acid (rRNA) region and multilocus sequence analysis (MLSA) of seven highly conserved genes, dnaG, gyrB, mutS, nusG, rplA, rpoB and tufB . The MLSA mapping approach described in this article was able to discriminate between two ' Ca . Liberibacter' species within a metagenomic data set and represents a novel approach to detecting and differentiating unculturable species of liberibacter. Further, CLbr can confound the Li et al . (2006) quantitative PCR (qPCR) diagnostic tests for CLas and CLaf. Abstract : A novel species of the liberibacter genus, ' Candidatus Liberibacter brunswickensis' (CLbr) was identified in the Australian eggplant psyllid, Acizzia solanicola . CLbr forms a unique clade in the liberibacter genus based on phylogenetic analysis of the 16S ribosomal ribonucleic acid (rRNA) region and multilocus sequence analysis (MLSA) of seven highly conserved genes, dnaG, gyrB, mutS, nusG, rplA, rpoB and tufB . The MLSA mapping approach described in this study was able to discriminate between two Ca . Liberibacter species within a metagenomic dataset..